Use of serum bilirubin/albumin ratio for early prediction of bilirubin induced neurological dysfunction - Dalia Mosallam; Reem N. Said; Marwa A. Abd Elsamad; Nada M. Abdelfatah (SpringerOpen, 2019)
Abstract Background Kernicterus or bilirubin encephalopathy is a preventable cause of handicap, still occurs in our country. The aim of the current study was to assess the role of bilirubin/albumin ratio in improving the morbidity of the cases with unconjugated hyperbilirubinemia and to estimate of the cutoff value for B/A ratio for prevention and early management of bilirubin-induced neurological dysfunction. Results The mean gestational age was 37.1 ± 2.11 weeks; the mean age of onset of jaundice was 2.36 ± 1.04 days; the mean level of total bilirubin was 26.14 ± 7.36 mg/dl. At chosen cutoff value of bilirubin albumin ratio (B/A) 6.68, sensitivity was 82% while specificity was 64% and accuracy was 95%. Conclusion Bilirubin encephalopathy still occurs in significant number in our country though it is a preventable cause of handicapping. TSB is a sensitive but not a specific indicator of ABE, B/A ratio is more specific indicator of the neurologic outcome and should be utilized in the decision of early intervention.